Entrepreneurship in the public sector in the post-pandemic: the online judiciary (Research, Society and Development, 2022)
The viral pandemic caused by Covid-19 changed the daily routine of people, as well as companies, whether public or private. Extreme measures have become necessary to contain the spread of the virus, and social isolation must be promoted. This reality affected the already overloaded Brazilian Judicial System, requiring the modernization and improvement of services provided to society. Thus, the aim of this study was to understand entrepreneurship as innovation in the public sector, especially in the judiciary. The methodology used to develop the work was the literature review, through consultations with books, legislation, publications of the Brazilian Government and articles published in journals in the area. It can be concluded that the pandemic accelerated the process of modernization of the public sector, especially the judiciary, using tools such as telework and artificial intelligence. Therefore, it was observed that it is necessary entrepreneurship and strategic planning for these sectors to be able to function efficiently, with these new technologies, to provide a quality service, even in the face of a state of public calamity.